Pengaruh Profitabilitas, Kepemilikan Publik, Opini Publik Dan Ukuran Perusahaan Terhadap Ketepatan Waktu Pelaporan Keuangan Perusahaan Di Bursa Effek Indonesia - Fitria Marisya (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The purpose of this study was to determine the effect of profitability, public ownership, public opinion and company size on the timeliness of company financial reporting on the Indonesian Stock Exchange. The objects taken in this study are ten sub-sectors of companies listed on the Indonesia Stock Exchange (IDX) which are grouped into two categories based on the timeliness of the company's financial reporting for the period 2016, 2017, and 2018, namely: Companies that are timely in their financial reporting to Bapepam -LK, and companies that are not timely in their financial reporting to Bapepam-LK. The variables used in this study can be classified into two, namely: Dependent Variables, In this study the dependent variable is timeliness (Y). Independent Variables (Independent Variables). In this study the independent variables are Profitability (X1), Public Ownership (X2), Audit Opinion (X3), and Company Size (X4). Based on the output results above, the DW value generated from the regression model is 1.936. The amount of data (n) = 30, seta k = (5) (k is the number of independent variables) obtained the value of du of 1.835 and dL of 1.071. Then the autocorrelation value is between 1.835 < 1.936 < 2.165 so there is no autocorrelation.